Wide field electromagnetic method calculation in arbitrary orientation and its effectiveness analysis - Tian, Hongjun; Qiang, Jianke; Li, Kun; Tan, Zhangkun; Zhang, Ying; Zhu, Dexiang (Frontiers in Earth Science, 2023)
The wide field electromagnetic method E_Ex observation method requires the horizontal electrical field source (AB) to be parallel to the measure station (MN), but the complex terrain conditions make it difficult to meet the AB parallel MN in field construction, and there is always an azimuthal difference α between them, which will bring a large calculation error and cause distortion of the interpretation parameters if the calculation method E_Ex continues to be used. In order to tackle this problem, we analyse and study the E_Ex method and derive the new calculation method of E_EMN for the wide field electromagnetic method along the MN (E_EMN). The method is based on the intrinsic relationship between the electric field components Ex, Ey and the azimuthal difference α and derives the expression for the electric field E_EMN along the MN direction, and then uses the E_EMN to calculate the wide field apparent resistivity. In this paper, we design a three-layer geoelectric model and calculate the azimuthal angle difference α = 0° and α = 15°wide field apparent resistivity parameters, respectively. The results show that the relative error between the calculated apparent resistivity and the theoretical value is less than 1%, which verifies the correctness and validity of the method. To further verify the accuracy of the method, experimental work on azimuthal difference α was carried out next to a known well in Sichuan. The results show that: firstly, when α is 1°, 3°, 5°, 10°, and 15°, respectively, the relative error of each frequency point increases with α increasing. Secondly, when α is 1°, 3°, 5°, 10°, and 15°, respectively, the relative error of each frequency point is less than 10% when the EMN method is used to calculate the wide field apparent resistivity value; thirdly, taking α = 15° as an example, single-station inversions are performed with Ex and EMN apparent resistivity parameters, in which the Ex inversion results are more different from the trend of the logging curve, while the EMN inversion results are relatively more consistent with the trend of the logging curve. The arbitrary orientation EMN calculation method proposed in this paper can effectively reduce the influence of α on the interpretation parameters and improve the accuracy of interpretation, and also greatly expand the applicability and flexibility of Ex wide field electromagnetic method in the observation of complex terrain areas, which has important theoretical research and practical production significance.